Relationship between Knowledge Level of Clean and Healthy Living Behaviour (PHBS) with Dental and Oral Hygiene at the Quranic House Bustanul Mustafa Lhokseumawe - Syafrida, Anita; Deriansyah, Muhammad; Fardian, Nur; Yasin, Muhammad; Naufal, Muhammad Andre; Nasywa, Irandary (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Dental and oral health is the healthy condition of the hard and soft tissues of the teeth and related elements in the oral cavity. This study aims to analyze the relationship between the level of knowledge regarding Clean and Healthy Living Behavior (PHBS) and dental and oral hygiene among students at Rumah Quran Bustanul Mustafa Lhokseumawe. This research uses a descriptive correlation design with a cross-sectional approach. The sample consisted of 62 students selected using purposive sampling technique. The instruments used include a questionnaire to measure the level of PHBS knowledge, which has been tested for validity and reliability, as well as a dental and oral hygiene observation sheet using the OHI-S (Oral Hygiene Index-Simplified) index. Data analysis was carried out using the Spearman correlation test with a significance level of 0.05. The results of the study showed that there was a significant relationship between the level of PHBS knowledge and oral hygiene with a value of p = 0.000 (<0.05). The correlation value of -0.654 shows a strong and negative relationship, where the higher the student's level of knowledge, the better their level of dental and oral hygiene. The distribution of knowledge levels shows that 48.38% (30 students) have good knowledge, 32.26% (20 students) have sufficient knowledge, and 19.36% (12 students) have poor knowledge. Meanwhile, students' oral hygiene showed that 29.04% (18 students) had good hygiene, 38.70% (24 students) had sufficient hygiene, and 32.26% (20 students) had poor hygiene. In conclusion, there is a significant relationship between the level of PHBS knowledge and dental and oral hygiene among students at Rumah Quran Bustanul Mustafa Lhokseumawe. These results emphasize the importance of PHBS education to improve children's dental and oral health.